Fecal Microbiota and Diet of Children with Chronic Constipation - Joyce Gomes de Moraes; Maria Eugênia Farias de Almeida Motta; Monique Ferraz de Sá Beltrão; Taciana Lima Salviano; Giselia Alves Pontes da Silva (Hindawi Limited, 2016)
Many factors explain dysbiosis in chronic constipation (CC), such as a low-fiber diet. The objective of this study was to compare the fecal microbiota of constipated and nonconstipated children and their intake frequencies of food. Methods. This observational study included 79 children (M/F 43/36) aged six to 36 months divided into two groups: cases (39 constipated children) and controls (40 nonconstipated children). We used a structured form to collect demographic variables, conducted anthropometric assessment, and collected food intake frequency data. The fecal microbiota of the stool samples was analyzed by real-time polymerase chain reaction (PCR) using the fluorophore SYBR® Green. Results. Constipated children had a smaller concentration of Lactobacillus per milligram of stool (p=0.015) than nonconstipated children, but the concentration of Bifidobacterium per milligram of stool (p=0.323) and the intake of fruits, vegetables (p=0.563), and junk food (p=0.093) of the two groups did not differ. Constipated children consumed more dairy products (0.45±0.8; p>0.001), were more frequently delivered via caesarean section (69.2%), were weaned earlier (median: 120; 60Q1-240Q3), and had a family history of constipation (71.8%). Conclusions. Children with CC have a smaller concentration of Lactobacillus in their stools and consume more dairy products.